Test of lepton flavor universality with B0s → 𝜙ℓ+⁢ℓ− decays - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Physical review letters, 2025)
Lepton flavor universality in rare 𝑏 →𝑠 transitions is tested for the first time using 𝐵0𝑠 meson decays. The measurements are performed using 𝑝⁢𝑝 collision data collected by the LHCb experiment between 2011 and 2018, corresponding to a total integrated luminosity of 9 fb−1. Branching fraction ratios between the 𝐵0𝑠→𝜙⁢𝑒+⁢𝑒− and 𝐵0𝑠 →𝜙⁢𝜇+⁢𝜇− decays are measured in three regions of dilepton mass squared, 𝑞2, with 0.1<𝑞2<1.1, 1.1 <𝑞2 <6.0, and 15<𝑞2<19 GeV2/𝑐4. The results agree with the standard model expectation of lepton flavor universality.